"Home-buying behaviour model of Generation Y in Turkey". Issue 5 (5th September 2019) - Kayapinar Kaya, Sema; Ozdemir, Yasal; Dal, Murat
Abstract : Purpose: The young population in Turkey is gradually increasing. Generation Y, which comprises the people born between 1980 and 1999 (Broadbridge et al., 2007 ) and free-spirited and tech-savvy, forms a large part of the population of the world, especially Turkey, and is of great importance to the housing sector for their home-buying preferences. In this study, housing preferences of students in Turkey's two socio-economically different universities were comparatively analysed through quantitative methods. Design/methodology/approach: A survey was simultaneously distributed among students of two universities. The survey consists of six main factors: "reliability", "economic opportunities", "transportation opportunities", "quality of life and social opportunities", "quality standards", and "technological opportunities", with 25 statements. The questionnaire was developed through a comprehensive literature review and the opinions of university stakeholders. Findings: Results showed that the structure of the family and socio-economic differences affect home-buying preferences. The Mann–Whitney U test indicated that there was a meaningful difference of opinion between students of two universities. Munzur University students paid attention to economic opportunities when buying a home. Additionally, there was a meaningful relationship among the age groups in factors of "having a parking place" ( p = 0.026) and "having a playground" ( p = 0.026). As the age increases, students desire a playground around their future home. Research limitations/implications: The most important limitation of this study is the non-parametric data. Non-parametric data structure and the tests performed accordingly are less preferred than parametric data structure. For that reason, to what extent the results accurately represent Generation Y needs to be assessed through future study. Also, a certain number of sampling could be reached as purposive sampling was used. Originality/value: This study contributes to the literature in terms of comparatively analysing buying preferences of Generation Y through statistical methods and showing the relationship between these preferences and socio-economic features statistically. Due to the insufficient quantitative research on the literature, this quantitative study was carried future home-buying preferences of Generation Y university students, who will also be actively involved in the housing market. The purpose of this study investigates marketing factors that affect housing preferences of students in Turkey.